Hubungan Kadar Glial Fibrillary Acidic Protein Serum dengan Skor Nihss dan Ich Score pada Pasien Stroke Hemoragik - Dicky Lesmana; Syarif Indra; Restu Susanti; Yuliarni Syafrita; Dedi Sutia; Lydia Susanti (Jurnal Ners, 2026)
Hemorrhagic stroke, particularly intracerebral hemorrhage (ICH), is a major cause of mortality and morbidity and is associated with poorer outcomes than ischemic stroke. The severity of ICH is commonly assessed using the National Institutes of Health Stroke Scale (NIHSS) and the ICH score. Glial fibrillary acidic protein (GFAP) is an astrocytic protein released into the circulation as a result of glial tissue injury and is known to be elevated in various types of stroke, with generally higher concentrations in ICH. This study aimed to evaluate the potential of GFAP as an indicator of disease severity and clinical outcomes in ICH. This was an observational analytic study with a cross-sectional design conducted in patients with hemorrhagic stroke hospitalized at RSUP Dr. M. Djamil Padang from February to July 2025. Serum GFAP levels were measured using the ELISA method, while disease severity and mortality were assessed using the NIHSS and ICH score. Statistical analysis was performed using one-way ANOVA or the Kruskal–Wallis test to examine the relationship between GFAP and NIHSS, and Pearson or Spearman correlation tests to evaluate the relationship between GFAP and the ICH score. Most subjects had moderate stroke severity based on the NIHSS (48.57%). The median serum GFAP level was 3.41 ng/mL (1.75–17.7). Analysis showed a significant difference in GFAP levels across the three NIHSS severity categories (p = 0.001), particularly between the mild–severe (p = 0.002) and moderate–severe (p = 0.001) groups. Spearman correlation analysis demonstrated a significant positive correlation between GFAP levels and the ICH score (p = 0.000; r = 0.481). In addition, GFAP levels were significantly higher in patients with hemorrhage volumes >30 cc compared with those ≤30 cc (median 7.29 vs 3.24 ng/mL; p = 0.000). Serum GFAP levels were significantly associated with NIHSS score, ICH score, and hemorrhage volume in patients with hemorrhagic stroke. These findings support the use of GFAP as a biomarker for assessing severity and prognosis in hemorrhagic stroke.